Education and acute coronary syndromes: results from the CARDIO2000 epidemiological study - Pitsavos Christos E.; Panagiotakos Demosthenes B.; Chrysohoou Christina A.; Skoumas John; Stefanadis Christodoulos; Toutouzas Pavlos K. (The World Health Organization, 2002)
OBJECTIVE: As a measure of socioeconomic status, low educational level is positively associated with the risk of developing adverse health events. The aim of this study was to investigate the relationship between the level of education and the risk of developing non- fatal acute coronary syndromes. METHODS: During 2000 and 2001, 1619 randomly selected subjects from several regions of Greece were entered into a case-control study. Of these, 750 were patients with their first acute coronary heart syndrome event, and 869 were hospitalized controls with no cardiovascular disease in their medical history. Trends in cardiovascular risk factors were then examined across patient and control educational level by years of schooling. FINDINGS: In both patients and controls, education status was related to economic and occupation status, smoking habits, physical inactivity, alcohol consumption and non-compliance to treatment. After adjusting for these and other conventional risk factors, as well as for the effects of age and sex, we found that coronary risk increases by 82% (odds ratio (OR) = 1.82, P <0.05) for individuals with a lower level of education, and by 65% (OR = 1.65, P <0.05) for individuals with an average education, compared to those with an academic education. CONCLUSIONS: Although the least-educated subjects adopted a more adverse lifestyle than the more-educated subjects, the inverse association between education and coronary risk was independent from such factors. The inverse association may be due to psychosocial differences, and prospective cohort studies are needed to confirm or refute these results.